2019
DOI: 10.3390/ani9121089
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Validation of Computer Vision Techniques to Assess Heart Rate, Eye Temperature, Ear-Base Temperature and Respiration Rate in Cattle

Abstract: Precision livestock farming has emerged with the aim of providing detailed information to detect and reduce problems related to animal management. This study aimed to develop and validate computer vision techniques to track required features of cattle face and to remotely assess eye temperature, ear-base temperature, respiration rate, and heart rate in cattle. Ten dairy cows were recorded during six handling procedures across two consecutive days using thermal infrared cameras and RGB (red, green, blue) video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…RGB videos were processes by the respective algorithm, which identifies changes in luminosity in the green colour channel within the ROI (eye area; Figure 1c) and applies a second-order Butterworth filter and a fast Fourier transformation (FFT) after the signal has been obtained. To improve the accuracy of this analysis, the ROI was tracked through a computer vision algorithm following the methodology suggested by Jorquera-Chavez et al [25]. This methodology first selects the most representative features within the ROI by using different pattern recognition techniques which then are tracked along with the sequential frames of the video.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RGB videos were processes by the respective algorithm, which identifies changes in luminosity in the green colour channel within the ROI (eye area; Figure 1c) and applies a second-order Butterworth filter and a fast Fourier transformation (FFT) after the signal has been obtained. To improve the accuracy of this analysis, the ROI was tracked through a computer vision algorithm following the methodology suggested by Jorquera-Chavez et al [25]. This methodology first selects the most representative features within the ROI by using different pattern recognition techniques which then are tracked along with the sequential frames of the video.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for the analysis of respiration rate, non-radiometric infrared videos were processed using an algorithm that identifies the changes in pixel intensity values within the ROI (nose area; Figure 1d), which are related to the air exchange during exhalation and inhalation [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are currently investigating non-contact computer-based techniques to monitor HR in livestock [119]. A low to high correlation coefficient (0.09-0.99) was found between HR obtained from the red, green and blue color channels (RGB) videos and from the gold standard method in cattle [120]. The study also showed that the accuracy of HR measurement is related to both the position of the cameras and the area analyzed on the images.…”
Section: Animal Hr Monitoring Techniquesmentioning
confidence: 96%
“…To date, many signal processing techniques have been proposed to remove MAs in PPG signals. Adaptive noise cancellation (ANC) is a popular approach to remove MAs where reference signals can be constructed from acceleration data or another PPG signal [39,[120][121][122][123][124][125][126][127][128][129][130][131][132][133]. However, the drawback is that the performance of ANC is sensitive to the reference signal, and it is difficult to reconstruct qualified reference signals during exercising.…”
Section: • Motion Artifacts Removalmentioning
confidence: 99%